Deconversion and Identity Formation in Adolescents: The Role of Internal Dialogs and Religiousness of Parents. Issue 4 (2nd October 2022) - Puchalska-Wasyl, Małgorzata M.; Łysiak, Małgorzata; Zarzycka, Beata
ABSTRACT: Adolescence is a period of exceptional sensitivity to the ideals that are subject to verification. Therefore, a phenomenon of deconversion (i.e. abandonment of religion) is observed among adolescents. The paper aims to analyze deconversion and its connections with the identity formation as well as mediators and moderators of these relationships. Participants were 272 adolescents aged between 14 and 18. Three scales were used: the Circumplex Identity Modes Questionnaire, the Internal Dialogical Activity Scale-Revised, and the Adolescent Deconversion Scale. We found that identity modes such as moratorivity, diffusion, and defiance are positively related to deconversion, whereas socialization and normativity are negatively related to deconversion. The negative relationships between normativity and deconversion exist if the parent (especially mother) is assessed as religious or very religious. Moreover, internal dialogs moderate and mediate links between different identity modes and dimensions of deconversion.